Analysis of efficacy and safety of linezolid-based chemotherapeutic regimens for patients with postoperative multidrug-resistant spinal tuberculosis - Jie Qiao; Lin Yang; Jing Feng; Xiyong Dai; Feng Xu; Ping Xia (International Journal of Infectious Diseases, 2022)
Objectives: The study aimed to explore the efficacy and safety of linezolid-based chemotherapeutic regimens for patients with postoperative multidrug-resistant spinal tuberculosis. Methods: The randomized controlled study included 50 Mycobacterium tuberculosis culture or pathological-confirmed multidrug resistant tuberculosis patients who received spinal surgery from January 2018 to February 2020. Twenty-five patients were assigned to the control group and the study group, respectively. Random number method was used for patient allocation and they were treated with levofloxacin, pyrazinamide, thioisonicotinamide enteric-coated tablet, amikacin sulfate injection, and sodium p-amino salicylate injection, accompanied by linezolid or not. Results: The overall effective rate of the study group was higher than that of the control group (88.00% vs 64.00%, P<0.05). The severity of pain at 3 and 6 months postoperatively was lower in the study group than that in the control group (P<0.05). Postoperatively, the study group had higher bone graft fusion rate, shorter mean bone graft fusion time, and higher paraspinal cyst absorption rate than the control group (P<0.05). Postoperatively, the study group had lower levels of PCT, ESR, and CRP than the control group (P <0.05). All patients had normal hepatic and renal function, and no statistical difference of adverse effects between 2 groups were found. Conclusions: Linezolid-based chemotherapeutic regimens can effectively treat patients with postoperative multidrug-resistant spinal tuberculosis but have higher rates of adverse reactions.